Optimization of Electric Multiple Unit Headway - Ruliyanta Ruliyanta; Fahmi Idris; Adhyartha Usse Keraf (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
The needs of the people of JABODETABEK, Indonesia, for fast, safe, and comfortable means of transportation, such as electric rail trains, are increasing. In 2023, the narrowing of the headway on the East Bekasi-Cikarang station route will cause frequent tripping of the traction substation. This is due to the increasing frequency of multiple electric unit trips and the lack of power capacity at the traction substations to supply electrical power. In addition to that, there is a voltage drop in the overhead power network because the distance between the traction substations is too long. The fastest headway is 3 minutes from the original 13 minutes. This research aims to optimize the power capacity of the traction substation in the LAA 1.10 Cikarang area. The method is load flow analysis using ETAP 19.0.1 software. Results of the design for adding the Tambun Insertion substation and the Telaga Murni Insertion substation. On a 3-minute headway, the average voltage drop increased by 22.5% on the East Bekasi - Cibitung route from 1,222 VDC to 1,497 VDC. Meanwhile, the Cibitung-Cikarang route, originally 1,282 VDC, became 1,494 VDC, or an increase of 16.5%.